Mycobacterium vaccae immunization to OVA sensitized pregnant BALB/c mice suppressed placental and postnatal IL-5 and inducing IFN-gamma secretion - AKKOÇ, TUNÇ (TAYLOR & FRANCIS INC, 2008)
Although the development of atopy in the newborn is determined by a multitude of factors, an intense Th1 stimulus early in life could be protective by facilitating a switch away from Th2. Aimed to determine the effect of single Mycobacterium vaccae (M. vaccae) immunization to OVA-sensitized pregnant mice on IL-5 and IFN-gamma secretion from placental lymphocytes and splenocytes of offspring. Pregnant BALB/c mice were divided into 4 groups, OVA-sensitized + M. vaccae immunized, OVA-sensitized, M. vaccae immunized and controls. Sensitization with OVA was initiated before mating, and aerosol OVA challenge were performed during pregnancy. M. vaccae immunization was performed on the 12(th) day of pregnancy. IL-5 and IFN-gamma levels of placental lymphocytes were analyzed on the 18(th) day of pregnancy and splenocytes of offspring on the 2(nd) and 28(th) days during postnatal period. A single administration of M. vaccae to OVA-sensitized pregnant mice downregulated IL-5 secretion and induced IFN-gamma secretion from placental lymphocytes. On the other hand, after M. vaccae immunization downregulation of IL-5 levels and upregulation of IFN-gamma secretion persisted in offspring when determined on 2(nd) and 28(th) days of life. Vaccination with M. Vaccae to OVA-sensitized pregnant BALB/c mice prevented Th2 immune responses by enhancing secretion of IFN-gamma and lowering IL-5 levels during pregnancy and the effect persisted during the postnatal period in offspring.
Keywords: hygiene hypothesis; interferon gamma; murine model of asthma; Mycobacterium vaccae; ovalbumin; pregnancy; ALLERGIC SENSITIZATION; ATOPIC-DERMATITIS; BCG VACCINATION; MURINE MODEL; CHILDREN; ASTHMA; INFLAMMATION; CYTOKINES; OVALBUMIN; DISEASE